Mobile app to play team-building games - Liew, Zi Xun (2019)
As the world evolves and technology advances, it becomes inherent that technology plays a huge part in people’s everyday lives and one such area is team building. Distributed teams are commonplace in today’s workplace, and these virtual teams rely heavily on computer-mediated communication as their primary means of communication, making physical team building games harder to conduct. As a result, people are switching to using mobile devices as a platform for games. With the rise of mobile device usage in today’s digital age, it will be meaningful to utilise mobile devices, such as smartphones or tablets, as a platform for team building games. By doing so, not only will it be easier and more efficient for these games to be organised, but participants are also not restricted by the physical space constraints that are present in physical games. This project aims to develop an online multiplayer mobile game which promotes team building by enhancing creative problem solving and fostering interpersonal relations. The well-known physical Tangram game will be converted into a multiplayer mobile game that allows for interaction between people through their mobile devices. The project includes the design and implementation of the Tangram game prototype to fit the multiplayer requirement, and also to show the possibility of converting a physical team building game to a digital team building game, with mobile devices as a platform.